De "ander" als steun en spanningsbron: De precaire praktijk van lichte steun aan mensen met een psychiatrische achtergrond vanuit een welzijnsvoorziening - Anne Elberse; Marc Hoijtink (Journal of Social Intervention: Theory and Practice, 2015)
The “other” as a source of both support and tension: the precarious practice of support for people with mental health problemsIn the 1960s, those living with mental health problems in the Netherlands stopped being placed into secluded institutions “in the woods”. Then, social policy began to aim at care in smaller institutions set in “normal” neighbourhoods. In the 1960s and 1970s, the general view was that it was not the person with mental health problems that needed to change, but rather that it was society that made this person ill. In the 1980s and 1990s, the focus of social policy shifted towards the individual and the notion that people with mental health problems need support from society to live like others. Nowadays, the expectation in social policy is that people with mental health problems should rely on their social networks and policy aims to increase the participation in society by those living with mental health problems.The empirical material in this paper is derived from a small-scale study that evaluated a programme called “Koffie om de Hoek” (Coffee around the corner), a place where people who have, or have had, mental health problems can meet in a community centre. The goal of Koffie om de Hoek is to minimize the barriers that users may experience when they want to participate in activities in their neighbourhood and wider society. Koffie om de Hoek focuses on people with mental health problems, but everyone who feels comfortable is welcome. Koffie om de Hoek started more than 10 years ago and it was only evaluated after the conclusion of the pilot period. Considering all the changes that have occurred in the social care sector, it was expected that there would be an increased need for facilities such as Koffie om de Hoek. However, visitor numbers were decreasing. Why do people come to Koffie om de Hoek? And why do some drop out, or not come at all? This was translated into the following research question: “What sources of support and tensions do people with mental health problems experience in their use of Koffie om de Hoek?” As part of the research, 13 semi-structured interviews were conducted within three different groups: six people who regularly visit Koffie om de Hoek, five people who used to visit Koffie om de Hoek but dropped out, and two people who have (or previously had) mental health problems but never visited Koffie om de Hoek. The results were analysed using MAXQDA, and were discussed in two focus groups with professionals involved in Koffie om de Hoek. The results of this research were also discussed with other similar facilities in the region, and this showed that the results are also relevant for other facilities.Five important results presented in this article illustrate the precarious role of services such as Koffie om de Hoek. The first finding is that one important reason for people to visit Koffie om de Hoek is to be around other people. For some participants, going to Koffie om de Hoek is the only occasion in the week that they leave the house to join in a social setting. Secondly, the study made previously invisible barriers to coming to Koffie om de Hoek visible. For example, participants find it difficult to come to Koffie om de Hoek by themselves, but they find it much easier to come if accompanied by someone they are familiar with. Thirdly, this study showed that the participants are sensitive to the behaviour of “others” (other visitors as well as professionals), and this can become a source of tension. For example, they may find it difficult to deal with visitors who demand a lot of attention or behave unpredictably. But dealing with “the other” can also be a source of support: some of the participants appreciate the fact that most of the visitors at Koffie om de Hoek live with a mental health problem. Because of this, they can relate to each other better. A fourth result is that participants visiting Koffie om de Hoek experience it as a place where they do not need to live up to many expectations from other people, and as a place where they feel that they can be “themselves”. The last important finding was that this study raised many individual questions. People asked for support regarding participation in society. For example with questions on how to become a volunteer or on how to deal with other visitors that they had problems with.This article shows why supporting people with mental health problems is such a precarious practice. In social policy, services like Koffie om de Hoek are often seen as a first step towards “participation” in society. However, this also poses a risk from a professional and policy perspective: expectations may be high and people may leave Koffie om de Hoek because of the pressure they experience, without having developed the skills to actually participate. Koffie om de Hoek needs to remain a place where people are free from what they experience as pressure and where there is consideration for each person’s different needs and possibilities. Some of the (potential) visitors even need help to make contact and stay in contact with other people at Koffie om de Hoek, or with people in general.The article also describes the role of evaluating studies in the social sector and the importance of involving visitors as well as committed professionals in these studies. Small-scale qualitative research could play a greater role in improving facilities in the social sector. In the case of Koffie om de Hoek, it led to more motivated professionals, a better coordination with the needs of (potential) visitors and an increasing number of visitors to Koffie om de Hoek. This kind of research also produces important knowledge that is very relevant in social policy and in discussions on this topic. SAMENVATTINGDe "ander" als steun en spanningsbron: De precaire praktijk van lichte steun aan mensen met een psychiatrische achtergrond vanuit een welzijnsvoorzieningIn dit artikel staat een kleinschalig onderzoek naar de wijkvoorziening “Koffie om de Hoek” centraal. Koffie om de Hoek is een inloopmogelijkheid in een wijkcentrum, bedoeld voor mensen met een psychiatrische achtergrond. De voorziening heeft als doel de drempel om contacten te leggen en activiteiten te ondernemen buiten de wereld van de GGZ te verkleinen. Aan de hand van de vijf belangrijkste onderzoeksbevindingen wordt geïllustreerd hoe precair de praktijk van lichte steun is binnen deze voorziening. Bezoekers ervaren professionals en andere mensen die gebruik maken van de voorziening als een belangrijke bron van steun, maar de omgang met “de ander” (de andere bezoekers en professionals) kan ook tot spanningen leiden. Die kunnen zo hoog oplopen dat bezoekers afhaken, zelfs wanneer de voorziening het enige moment in de week biedt waarop zij contact hebben met “de ander”. In het laatste deel van het artikel wordt stilgestaan bij de betekenis van de bevindingen voor de voorziening en wordt ervoor gepleit om gebruikers en professionals in zorg en welzijn nadrukkelijker bij evaluatief onderzoek te betrekken dan doorgaans het geval is.